The Role of Financial Aid Programs and Education Facilities in Overcoming Education Gaps in Central Java Rural Schools - Haslinda Mokodompit; Arkam Lahiya; Tiara Fathulmila Matiala; Adit Mohammad Aziz; Sabil Mokodenseho (Jurnal Pendidikan West Science, 2023)
This study investigates the role of financial aid programs and educational facilities in addressing education gaps in rural schools in Central Java through quantitative analysis. The study of 150 students used correlation and regression analysis to explore the relationship between financial aid, perceived quality of educational facilities, socioeconomic status, and academic performance. Descriptive statistics reveal a diverse sample, and correlation analysis shows a positive relationship between financial aid, educational facilities, and academic performance. Regression analysis further highlights the individual contribution of financial aid and facilities to academic success, with additional emphasis on their combined impact. The results underscore the importance of comprehensive interventions that can address financial barriers and infrastructure shortages. Policymakers, educators, and stakeholders can use these findings to inform targeted strategies to promote educational equity in schools in rural areas in Central Java.